Performance In The Implmentation Of Online Single Submission (OSS) At The Investment And One-Door Integrated Services Department Of Bantaeng Regency - Asrah, Nurul Husna; Herman H; Suarlin (International Journal Of Public Policy and Bureaucracy, 2024)
This study aims to evaluate the performance of the Online Single Submission (OSS) system implemented by the Investment and One-Stop Integrated Service Office (DPMPTSP) in Bantaeng Regency. Using a qualitative research approach, data were collected through observation, interviews, and documentation to assess the effectiveness of OSS implementation based on five key performance indicators: input, process, output, results, and benefits. The findings highlight that the existing facilities and infrastructure at the DPMPTSP Office are adequate to support the implementation of OSS. The licensing procedures facilitated by the OSS system have been designed to enhance public service delivery, simplifying previously complex processes. However, several operational challenges remain, particularly in optimizing technology use and user understanding of the system. Licenses processed through the OSS framework are typically completed within one to three days, demonstrating efficiency and responsiveness, although this depends on the completeness of the required documents and the users’ capacity to navigate the system. The implementation of the OSS system has successfully achieved its intended objectives, including improving public service quality by integrating structural factors such as technological advancement, regulatory frameworks, and standard operating procedures (SOPs). Functional factors, including improved user capacity and skilled human resources, further contribute to the system's success. Additionally, the OSS system has significantly enhanced transparency, convenience, and speed in licensing services, making it a vital tool in the modernization of public administration. Despite these successes, the study identifies several obstacles in the implementation process. Key challenges include limitations in technological infrastructure, inadequate operational resources, and inefficiencies in inter-agency coordination, which hinder the full potential of the OSS system. Supporting factors, such as effective cross-agency coordination, are critical in ensuring data synchronization and seamless service delivery. Overall, the implementation of the OSS system in Bantaeng Regency has positively impacted public service quality. However, achieving maximum performance will require stronger investments in resource allocation, infrastructure upgrades, and more robust collaboration across government agencies. Keywords: Performance, Implementation, Online Single Sumbmisson